The Impact of Progressive Movement in Saraiki "Kafi" - Perveen, Fauzia; Saleem, Muhammad (sourcecoder, 2024)
Kafi is a genre that is condidered the soul of Saraiki literature. Som researchers believe that kafi is a genre created to be song, hence it is also called musical melody. Mystic themes are usually written in it, whether it is in Saraiki language or Sindhi or Punjabi language, with the passage of time, Saraiki poets have adopted it to modern requirements, leading to changes in its subjects. Khawaja Farid elevated the Saraiki Kafi to its peak. From Khuram Bahawalpuri’s Kafi to Ahmad Aqeel’s the journey towards modernity signifies the survival of Saraiki poetry.